A study on the effectiveness of promotional tools by Persatuan Pengguna Islam Malaysia to create public awareness / Suretmi Sudirman - Sudirman, Suretmi (Faculty of Business and Management, 2009)
Promotion is very important to the organization whether it is profit or non-profit organization. This is because a good promotion may promise a good feedback from public and also the potential members towards the services that they offered to public especially for Muslims. This study focuses on "The Effectiveness of Promotional Tools by Persatuan Pengguna Islam Malaysia (PPIM) to Create Public Awareness". The objective is to determine the promotion tools that have given the greatest exposure to PPIM and also to establish the relationship between promotional mix and the effectiveness of promotional tools that had been implemented by PPIM. The sampling technique that has been used was the non probability sampling where 50 respondents were choose by the researcher using simple random sampling from PPIM database to answer the questionnaires. Besides that, correlation was conducted to determine the correlation between the promotional mix and the effectiveness of promotional tools. Findings in the study showed that advertising has given the big impact to PPIM and it is the most effective promotional tools. Meanwhile, the result shows that personal selling is the ineffective promotional tools.